UTILIZATION PROFANIZATION HERITAGE OF PETITENGET PURA CULTURE IN THE TRADITIONAL VILLAGE OF KEROBOKAN, KECAMATAN KUTA UTARA, BADUNG - Budiasih, Ni Gusti Ayu Nyoman (E-Journal of Cultural Studies; Volume 13, Number 3, August 2020DO - 10.24843/cs.2020.v13.i03.p04, 2020)
The study discusses the profanation of the utilization of cultural heritage of Petitenget Temple in the traditional village of Kerobokan, Sub-district of Kuta Utara, Regency of Badung, amid the rapid development of the tourism sector. The problems under study in this research pertaining to (1) the form of profanation of utilization of cultural heritage of Petitenget Temple in Kerobokan, (2) the factors that led to the profanation of the utilization of cultural heritage of Petitenget Temple in Kerobokan, (3) the impact and meaning of profanation of the utilization of cultural heritage of Petitenget Temple in Kerobokan. The research uses descriptive qualitative method of analysis, using several theories namely (1) theory of practice, (2) theory of deconstruction, (3) theory of commodification. Data collection in this study was conducted by using observation, interviews, and document research.         The research results show that Petitenget Temple as the cultural heritage has undergone profanation over its use as a cultural attraction in the traditional village of Kerobokan. The problems are due to several factors including (1) the appeal factor of Petitenget Temple as the heritage attractions, (2) the development of the tourism industry factors, with increasingly famous beaches around Petitenget Temple, (3) the factors of economic necessity in the management of Petitenget Temple. While the impact included (1) economic impact, (2) environmental impact, (3) social impact, (4) the impact of culture. While the meaning of profanation including (1) the meaning of sanctity of the temple, (2) the meaning of the ritual, (3) the meaning of moral, (4) the meaning of welfare. Keywords: profanation, cultural heritage, Petitenget Temple, and cultural tourism.